Desempenho agronômico de cultivares de cevada cervejeira sob diferentes lâminas de irrigação - Sanches, Fernando Mendes; Cunha, Fernando Franca da; Santos, Osvaldir Feliciano dos; Souza, Epitacio Jose de [UNESP]; Freitas Leal, Aguinaldo Jose; Theodoro, Gustavo de Faria (Univ Estadual Londrina, 2015)
The research work aimed to evaluate the performance of barley cultivars under different irrigation depths in Brazilian Cerrado. The experiment was conducted in a split plot completely randomized design, with irrigation depths (50, 75, 100 and 125% of crop evapotranspiration) in the plots and barley cultivars (BRS Sampa, BRS Manduri and BRS 195) in the split-plots, with four replications. Barley cultivars were different regarding number of tillers per plant, number of spikelets per spike, and root depth. The maximum yields for BRS Sampa, BRS Manduri and BRS 195 were 5,848; 5,449; and 4,767 kg ha(-1), respectively. BRS Sampa showed a value 17% higher than the yield reported by the holder. The irrigation depth affected all the agronomic traits. It is recommended BRS Sampa for Brazilian Cerrado, that didn't differ from other cultivars and was developed in region of similar climate; with replacement of 100% of crop evapotranspiration.

Objetivou-se avaliar o desempenho agronômico de cultivares de cevada cervejeira submetidas a diferentes lâminas de irrigação no cerrado sul-mato-grossense. O experimento foi conduzido no delineamento inteiramente casualizado, com parcelas subdivididas, tendo nas parcelas quatro lâminas de irrigação (50, 75, 100 e 125% da evapotranspiração da cultura) e nas subparcelas três cultivares de cevada (BRS Sampa, BRS Manduri e BRS 195), com quatro repetições. As cultivares de cevada diferiram apenas em número de perfilhos por planta, espiguetas por espiga e profundidade do sistema radicular. As produtividades máximas de grãos para as cultivares BRS Sampa, BRS Manduri e BRS 195 foram de 5.848, 5.449 e 4.767 kg ha-1, respectivamente. A cevada BRS Sampa apresentou valor 17% superior à produtividade divulgada pelo detentor. As lâminas de irrigação afetaram todas as características agronômicas avaliadas. Recomenda-se para o nordeste sul-mato-grossense a BRS Sampa irrigada com reposição de 100% da evapotranspiração da cultura, por não ter diferido das demais cultivares e ter sido desenvolvida para região de clima semelhante
Agronomic performance of barley cultivars under different irrigation depths
Keywords: BRS Sampa; Drip irrigation; Hordeum vulgare L.; Yield; BRS Sampa; Irrigação por gotejamento; Hordeum vulgare L., produtividade